2003
DOI: 10.1086/375810
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Early Structure Formation: Primordial Gas Clouds

Abstract: We use cosmological simulations to study the origin of primordial star-forming clouds in a ÃCDM universe, by following the formation of dark matter halos and the cooling of gas within them. To model the physics of chemically pristine gas, we employ a nonequilibrium treatment of the chemistry of nine species (e À , H, H + , He, He + , He ++ , H 2 , H þ 2 , H À ) and include cooling by molecular hydrogen. By considering cosmological volumes, we are able to study the statistical properties of primordial halos, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
737
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 552 publications
(791 citation statements)
references
References 64 publications
49
737
5
Order By: Relevance
“…We refer the reader to Abel et al (1997) for a derivation of the same, where the authors derive the photodissociation rate constant κ27 ∼ 1.1 × 10 8 s −1 , for a given value of an un-normalised flux (F in units of erg/s/Hz/cm 2 ). Thus, for our definition of J21, κ di = 4π10 −21 κ27 = 1.38 × 10 −12 s −1 (see Yoshida et al 2003). Thus Eq.…”
Section: H2mentioning
confidence: 93%
See 1 more Smart Citation
“…We refer the reader to Abel et al (1997) for a derivation of the same, where the authors derive the photodissociation rate constant κ27 ∼ 1.1 × 10 8 s −1 , for a given value of an un-normalised flux (F in units of erg/s/Hz/cm 2 ). Thus, for our definition of J21, κ di = 4π10 −21 κ27 = 1.38 × 10 −12 s −1 (see Yoshida et al 2003). Thus Eq.…”
Section: H2mentioning
confidence: 93%
“…At temperature below ∼ 8000 K, primordial gas in the early Universe cools most efficiently via molecular hydrogen to temperatures of ≈ few 100 K at which point the Jeans mass can be exceeded and gravitational runaway collapse of gas can proceed (e.g. Omukai & Nishi 1998;Abel et al 2002;Yoshida et al 2003). This channel of cooling is of importance for the formation of the first stars (Population III, or Pop III) in mini-haloes at z 10, which kick-start the metal enrichment of the inter-galactic medium and inter-stellar medium (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such simulations performed in the context of ΛCDM cosmologies have shown that the first stars (the so-called 'Population III') in the universe formed out of metal-free gas in dark matter minihalos of mass above a few ×10 5 M ⊙ (Abel et al 2000;Fuller & Couchman 2000;Yoshida et al 2003;Reed Abel et al 2002;Bromm et al 2002;see Bromm &Larson 2004 andFerrara 2005 for recent reviews). In Kuhlen & Madau (2005) we used a modified version of enzo, an adaptive mesh refinement (AMR), grid-based hybrid (hydro+N-body) code developed by Bryan & Norman (see http://cosmos.ucsd.edu/enzo/) to solve the cosmological hydrodynamics equations and study the cooling and collapse of primordial gas in the first baryonic structures.…”
Section: First Baryonic Objectsmentioning
confidence: 99%
“…For T vir ∼ < a few thousand kelvins the virialization shock is not ionizing, the free electrons left over from recombination are depleted in the denser regions, and the production of H 2 stalls at a temperature-dependent asymptotic molecular fraction x H2 ≈ 10 −8 T 1.5 vir ln(1 + t/t rec ), where t rec is the hydrogen recombination time-scale (Tegmark et al 1997). A typical H 2 fraction in excess of 200 times the primordial value is therefore produced after the collapse of structures with virial temperatures of order 10 3 K. This is large enough to efficiently cool the gas and allow it to collapse within a Hubble time unless significant heating occurs during this phase (Abel et al 2000;Yoshida et al 2003). Fig.…”
Section: First Baryonic Objectsmentioning
confidence: 99%
See 1 more Smart Citation